2018
DOI: 10.1016/j.jmmm.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between collective coordinate models for domain wall motion in PMA nanostrips in the presence of the Dzyaloshinskii-Moriya interaction

Abstract: Lagrangian-based collective coordinate models for magnetic domain wall (DW) motion rely on an ansatz for the DW profile and a Lagrangian approach to describe the DW motion in terms of a set of time-dependent collective coordinates: the DW position, the DW magnetization angle, the DW width and the DW tilting angle. Another approach was recently used to derive similar equations of motion by averaging the Landau-Lifshitz-Gilbert equation without any ansatz, and identifying the relevant collective coordinates afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…3), the average speed of a domain wall evaluated by the analytical model shows an offset of ≈30% with respect the average speed evaluated by Mumax3. This offset is in good agreement with the one evaluated in [16] and [19] for the two-collective coordinates model. It is observed that as the current density increases in the heavy metal layer up to a maximum of 3.5 × 10 11 A/m 2 , due to the SOT effect the average speed of a domain wall increases.…”
Section: A Model Validationsupporting
confidence: 87%
“…3), the average speed of a domain wall evaluated by the analytical model shows an offset of ≈30% with respect the average speed evaluated by Mumax3. This offset is in good agreement with the one evaluated in [16] and [19] for the two-collective coordinates model. It is observed that as the current density increases in the heavy metal layer up to a maximum of 3.5 × 10 11 A/m 2 , due to the SOT effect the average speed of a domain wall increases.…”
Section: A Model Validationsupporting
confidence: 87%
“…Our model should find applications in modelling DW dynamics in a wide range of contexts where DW velocities are not so high that spin wave emission from the moving DW [37][38][39] (not captured by our line model) becomes important, including creep motion of DWs [5] and Barkhausen noise [6]. Finally, extensions to bubble geometry would be useful, e.g., for studying effects due to the Dzyaloshinskii-Moriya interaction [40,41].…”
mentioning
confidence: 99%
“…1. Integrating ansatz 1 from 0 to π: This model does not take into account the canting in the domains, and was presented in one of our previous works [16]. 2.…”
Section: Collective Coordinate Modelingmentioning
confidence: 99%
“…Alternatively, simpler models may be extracted from the LLG equation to analyze the motion of specific topological defects of interest, such as vortices and DWs [8,9,10,11,12,13,14,15,16,17]. The sim-plified nature of these collective coordinate models (CCMs) is due to the introduction of an ansatz which characterizes the structure of the spin texture of interest.…”
Section: Introductionmentioning
confidence: 99%